Reduced-Nonlinear Effect on Magnetic Recording Channels Using MMSE Equalizers - A. Sirirungsakulwong; N. Puttarak; P. Supnithi (My University, 2015)
This paper considers the nonlinear effect on magnetic recording channels in order to reduce the system distortion. In this work, we propose the designed MMSE equalizer and target for a high density perpendicular magnetic recording to combat the nonlinear transition shift (NLTS) in a channel characterized by jitter noise and additive white Gaussian noise (AWGN). Due to a complex nature of nonlinear effects, the nonlinearity of a read-back signal is designed by the second order Volterra model consisting of linear and nonlinear part. The bit-error rate (BER) of the nonlinear-affected system using the designed MMSE equalizer is significantly decreased. The results show that the proposed minimum mean square error (MMSE) equalizer with constraint can decrease the inter-symbol interference (ISI) that causes nonlinearity and also improve performance.
Keywords: Perpendicular recording; Distortion (music); Blind Source Separation Techniques